Pengembangan Media Pembelajaran Interaktif Mata Pelajaran Bahasa Inggris Menggunakakn Aplikasi Adobe Animate Kelas VII Di SMP Negeri 3 Gorontalo - Latief, Mukhlisulfatih; Lahinta, Agus; H, Haeriani (Inverted: Journal of Information Technology Education, 2025)
This study aims to develop interactive learning media for English subjects for grade VIII students at SMP Negeri 3 Gorontalo using the Adobe Animate application. The research method used is Research and Development (RD) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The Analysis stage involves observation and interviews to identify the needs and problems faced by students and teachers in learning English. At the Design stage, learning media are designed by considering aspects of interactivity and ease of use. The Development stage produces interactive learning media products which are then tested through alpha and beta tests to obtain feedback from experts and users. Implementation was carried out in grade VIII of SMP Negeri 3 Gorontalo to test the effectiveness of the media in increasing student motivation and learning outcomes. The results of the study showed that interactive learning media based on Adobe Animate was effective in improving students' understanding of English comic dialogue material, as well as increasing students' motivation and interest in learning. This media also helps teachers in delivering material in a more interesting and interactive way. Thus, the development of this interactive learning media is expected to be an innovative solution in learning English at the junior high school level.